1999
DOI: 10.1046/j.1529-8817.1999.3561127.x
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Biological Processes in Coalescing Rhodophyta

Abstract: Sporeling coalescence in Gracilaria chilensis Bird, McLachlan et Oliveira produces genetically polymorphic, chimeric individuals. If this is common in red algae, it may have significant biological consequences. In this study, we evaluate the hypotheses that coalescence is widespread among the Rhodophyta and that specific and convergent morphological and ecological responses characterize this as a unique growth style among marine algae. A literature survey on coalescence was undertaken to assess the distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(98 citation statements)
references
References 31 publications
2
95
1
Order By: Relevance
“…DNA samples were amplified according to the protocol in Luo et al (1999), with slight modifications for Gv2CT . Although reports indicate that in many orders of red seaweeds, including Gracilariales, spores may coalesce and form a single, genetically chimeric plant (Santelices et al, 1999), no genotypes with supernumerary alleles were observed in this study.…”
Section: Study Populationscontrasting
confidence: 82%
“…DNA samples were amplified according to the protocol in Luo et al (1999), with slight modifications for Gv2CT . Although reports indicate that in many orders of red seaweeds, including Gracilariales, spores may coalesce and form a single, genetically chimeric plant (Santelices et al, 1999), no genotypes with supernumerary alleles were observed in this study.…”
Section: Study Populationscontrasting
confidence: 82%
“…Erect fronds may be up to 30 cm long and 5 cm wide. However, usually only 1 or 2 blades per plant reach a large size and there is a tendency for larger and thicker blades to be located closer to the center of the holdfast, generating size inequalities among the fronds arising from the same disc (Martínez & Santelices 1992, Santelices et al 1999. In this species, growth meristems are located along the border of the disc and at the base and borders of erect fronds.…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate whether coalescence was occurring among inter-and intraspecific contacting partners, ultrastructural studies were undertaken. Characterization of the process of coalescence at the cellular level followed (with modifications) the protocol described in previous studies (Santelices et al 1996(Santelices et al , 1999. Contacting holdfasts were carefully removed from the rocks about 30 d after contact, and fixed in the field for ultrastructural analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In many plants, somatic mutations accumulate between cell lineages (Whitham and Slobodchikoff 1981). Somatic mutations have also been reported in fungi (Peabody et al 2000;Stenlid 2000), red algae (Santelices and Varela 1993;Meneses et al 1999;Santelices et al 1999), invertebrates (Rinkevich and Weissman 1987;Barki et al 2002;Sommerfeldt et al 2003), and vertebrates (De 2011).…”
Section: Genetic Homogeneitymentioning
confidence: 98%